Ideologi Masyarakat Mempawah dalam Menyelaraskan Nilai Ritual Buang-buang pada Tradisi Robo-robo dengan Nilai Teologi Islam - Ahmad Sima Hanip Rahman; Mohd Arifullah; Pirhat Abbas; Nursaktila, Nia (Kartika: Jurnal Studi Keislaman, 2026)
The “Buang-buang” ritual is a central element of the Robo-robo tradition celebrated by the Malay community in Mempawah Regency, West Kalimantan. Although it is often perceived as an animistic practice, it in fact embodies complex and profound theological meanings. This study aims to explore the theological symbolism within the ritual and how the local community harmonizes ancestral traditions with Islamic teachings. The research employs a descriptive qualitative method with an ethno-theological approach, using participatory observation during the peak of the celebration, in-depth interviews with traditional leaders, religious figures, and representatives of non-governmental organizations, as well as analysis of historical documents of the Amantubillah Kingdom. The findings reveal that the “Buang-buang” ritual is not merely an offering to supernatural beings, but rather a symbolic expression of collective gratitude and repentance. The act of casting offerings into the river estuary is interpreted as an effort to discard negative traits, misfortune (balak), and egoism before entering a new year. This meaning aligns with the Islamic concept of tafaul (optimism toward goodness). The transformation of traditional chants into Islamic prayers further demonstrates cultural accommodation and the reinforcement of tawhid values within local cultural practices.